Optimization of dc-bus voltage regulation with grid con-nected single phase bi-directional converter - N. Ganesh, V; Ajay Daniel, J; Sivakumar, D; Balaji, S (International Journal of Engineering and Technology, 2018)
This paper presents using of alternate input energy source for optimization of DC bus voltage regulation and maintaining of availability of DC bus voltage with grid connected single phase bi-directional converter. Power generated by PV system and DC-DC boost converter with MPPT technology and fuzzy logic control for DC applications. Excess power available in the solar panel will return back to AC grid. DC power will be drawn from the AC grid when the intensity of sun is less. Maximum power output is obtained by using MPPT technique from PV panel. FUZZY controller is also used along with MPPT to control the final DC output voltage regulation of solar panel connected to the DC bus and for smooth power transfer. Simulation and actual experiments results are shared in detail for the implementation of MPPT with FUZZY controller and the modes of operation of Bi-directional converter.Â Â